The Lithuanian Nomenklatura of the Period of Stagnation in the Eyes of the Soviet “Governor General”: the Clash during the Appointment of Petras Griškevičius - Grybkauskas, Saulius (Genocidas ir rezistencija, 2012)
The article, based on the author’s conversation with Valery Charazov (born 1918), second secretary of the Lithuanian Communist party Central Committee (further LCP CC) 1967–1978, archive sources, and memoirs of other activists of that period, describes Charazov’s attitude to the situation in Soviet Lithuania after the death of the LCP CC first secretary Antanas Sniečkus, his evaluation of the Republic’s highest nomenklatura as well as his active role in appointing second secretary Petras Griškevičius as first secretary of LCP CC.Valery Charazov’s activity as LCP CC second secretary is similar to the activities of second secretaries of other republics, and it allows us to see the wider pattern of their activity throughout the Soviet Union. On the other hand, certain aspects allow us to see the Soviet Union–wide political processes from the local perspective of a republic. This is revealed though analysis of the actions of Charazov’s Lithuanian nomenklatura opponents – how they used their political connections with Ukrainian CP CC first secretary Shcherbitsky and with the Dnepropetrovsk political group which became entrenched during Leonid Brezhnev’s rule, as well as through the review of the political heritage of Antanas Sniečkus, who was also a client of the “shadow” USSR cardinal Mikhail Suslov.The article looks at the survey of the Lithuanian nomenklatura carried out by Valery Charazov. With this survey he sought to elect and present to Moscow the most suitable candidate to succeed Antanas Sniečkus. This survey and the character descriptions of candidates made in its wake was the informational basis that enabled the election of a candidate satisfactory to both Moscow and the local nomenklatura.The article presents the results of the survey carried out by Charazov. The following candidates were nominated for the position of LCP CC first secretary: chairman of the Council of Ministers of LSSR Juozas Maniušis, three LCP CC secretaries – Secretary for Industry and Construction Algirdas Ferensas, Secretary for Ideology Antanas Barkauskas, Secretary for Agriculture Rimgaudas Songaila – as well as the chairman of the party’s Vilnius city committee Petras Griškevičius, chairman of the LSSR labour unions’ committee Kazimieras Mackevičius, and head of LCP CC Organisational-party work division Vytautas Astrauskas. In the 47 interviews with contemporary party and Soviet leaders, the candidacy of Petras Griškevičius gained the most support. This activist was the first choice of 12 persons, and was considered a potential candidate (among others) – by 29 persons. Antanas Barkauskas was the first choice of one of those interviewed and was considered a possible candidate by 11 persons; Rimgaudas Songaila was no one’s first choice, but was seen as a possible candidate by 9 persons; Kazimieras Mackevičius, like Songaila, was not anyone’s preferred candidate, but 6 representatives considered him a possible candidate.Charazov’s survey revealed how unpopular Maniušis, who was viewed as one of the favourites, was. No one considered him as a first choice and 17 people considered him a possible candidate.Arguably, the main result of Charazov’s survey was the genuine characterisation of the nominees. It was distinguished from other formal responses of the time by the open identification of negative character traits of the candidates and a rather accurate description of their personalities.
Keywords: Lithuania; Soviet occupation; nomenclature; communist party